Ethical leadership and improved work behaviors: A moderated mediation model using prosocial silence and organizational commitment as mediators and employee engagement as moderator - Imam, Abeer; Kim, Do Yeong (Current Psychology, 2023)
Silence, which is a dysfunctional behavior, works to resolve potential problems if used positively. It serves to restrain employees from bombarding management with information overload or indulging in conflicts. This study aims to enhance our understanding of the role of ethical leadership, regarding academically positive behaviors mediated by prosocial silence and organizational commitment. A total of 325 faculty members from higher education institutions in Pakistan participated in this study. The results show that ethical leadership is positively related to academically positive behaviors in the workplace. Furthermore, prosocial silence and organizational commitment were found to mediate the relationship between ethical leadership and academically positive behaviors. Additionally, employee engagement moderated the enhanced positive relationship between ethical leadership and academically positive behaviors mediated by prosocial silence and organizational commitment. Our study finds that silence can have two faces referred to as Yin (negative) and Yang (positive). The Yang of silence (i.e., prosocial silence) works well under ethical leadership and promises positive organizational outcomes. The current study also finds that employees hide their concerns in support when they trust their leaders' ability to nurture a moral culture. Thus, this study extends the literature on the Yang of silence (i.e., prosocial silence) using a moderated mediation model to understand ethical leadership in improving academically positive behaviors in an Asian context. Furthermore, the theoretical and practical implications of these results are discussed.
Keywords: Cultural difference; Ethical leadership; Performance management; Prosocial silence; Social learning theory